La metropolización y sus desafíos para el actual ordenamiento territorial colombiano (2020)
Due to the rapid growth that has been occurring not only in the spatial coverage of cities but also in the number of people living in them, municipal interdependencies have become more evident in the eyes of governments and public policy makers. The social, economic and environmental dynamics of territories transcend established political-administrative limits, which shows the need for cooperation among local governments in favor of development. The Colombian regulations contained in the Organic Law of Territorial Ordering encourage coordination between the different territorial entities by offering the possibility of building different associative schemes as a strategy to overcome the municipalist conception. In the other regions of the country there has been a historical lack of adequate coordination for territorial planning and public investment. These development gaps are accentuated by the absence of a clear conception of how territorial entities should proceed with the phenomenon of metropolization...